Endoscopic closure after intraluminal surgery. Issue 5 (16th March 2017) - Akimoto, Teppei; Goto, Osamu; Nishizawa, Toshihiro; Yahagi, Naohisa
Abstract : Endoscopic submucosal dissection is established as a curative endoscopic method for gastrointestinal epithelial neoplasms with a high possibility of complete en bloc resection; however, postoperative adverse events of bleeding and delayed perforation remain. To prevent or minimize them, several techniques for endoscopic mucosal closure have been introduced, such as using endoscopic clips, combined use of hemoclips and supplement devices, and specially designed endoscopic suturing devices. Furthermore, endoscopic full‐thickness suturing technique for gastrointestinal wall defect has been developed based on the concept in natural orifice transluminal endoscopic surgery and endoscopic full‐thickness resection. Several closure techniques, including over‐the‐scope clip, threaded bars inserted in a hollow needle, stitches or staplers, and a curved needle and thread are reported. Secure closure of the iatrogenic defect may further expand the range of therapeutic endoscopy. Accumulation of evidence for the efficacy of endoscopic closure and establishment of these techniques are desired.